Identification of inoculated Arbuscular mycorrhizal fungi resistant to lead and zinc and their effect on some morphological traits of the Russian olive (Elaeagnus angustifolia L.) - Bahman Zamani Kebrabadi; Syed Mohammad Hojati; Farhad Rejali; Masoud Esmaeili Sharif; Hamid Reza Rahmani (علوم محیطی)
Introduction: Phytoremediation was introduced as an effective, inexpensive and environmentally friendly to remove, displace or disable pollutants from polluted soils. There are numerous physical and chemical methods for the treatment of heavy metal contaminated soils, which in addition to high costs, lead to the destruction of the physical and chemical structure and vital activities of the soil. This study was applied in order to investigate the effects of inoculated Arbuscular mycorrhizal fungi of resilience to lead and zinc on some morphological traits (colonization, diameter growth, shoot dry and fresh weight, root dry and fresh weight, height and leaf area) of Elaeagnus angustifolia L. Material and methods: One-year-old seedlings of E. angustifolia species with an average height of 70-50 cm, minimum diameter of 1-1.5 cm and leaf number of at least 30 were provided from Jebel Amelian nursery affiliated to the Natural Resources Office of Isfahan Province. The seedlings were transferred to the greenhouse of the Agricultural and Natural Resources Research Center of Isfahan Province and were kept there for 20 days to adapt to the new conditions. In doing so, six treatments of mycorrhizal fungi (Glomus versifome, G. etunicatum, G. intraradices, G. mossea, composition and control treatments) and five treatments of soil (naturally polluted soil, soil polluted with lead, soil polluted with zinc, soil polluted with lead and zinc, control (without pollution) treatment) were considered. Results and discussion: The results showed that there was a significant difference between the measured variables among the different treatment of mycorrhizal fungi. The highest and lowest colonization were observed for G. mossea (40.5%) and control treatment (25.6%), respectively. For G. mossea, the diameter growth (2.8mm), height (36.1cm) and leaf area index (28.8) increased in comparison to the control treatment. There was a significant difference between shoot dry and fresh weight and root dry and fresh weight in all of the treatment of mycorrhizal fungi. The highest dry and fresh weight of shoot was observed in G. mossea treatment (108.4 and 55 g) and the lowest was observed in control treatment (59.4 and 30.3 g). The highest and lowest of fresh weight were observed in control (95.3) and polluted soil with lead and zinc treatments (78g). Highest values of measured variables in all fungi and soil treatments were belonged to the inoculated treatment of G. mossea and the control treatment, respectively. Conclusion: Results of this study showed that inoculated treatment with G. mossea fungi and control treatment of soil caused the growth enhancement in E. angustifolia. However, there was no significant difference between mean fresh and dry weight of root and leaf area index in different soil treatments. Roots, as absorbent levels of water and food, have great effects on the absorption of water and various salts, and various environmental factors influence the growth of the plant through its effect on root growth. Heavy metal stress is one of the factors limiting root growth which affects plant growth activity. Also, in plants that were inoculated with mycorrhizal fungi, the mean of all measured variables was significantly higher than the control treatment. The highest shoot weight was observed in G. mosseae treatment, which suggests that G. mosseae contributed to the plant's absorption of water and food, especially phosphorus, and increased the accumulation of dry matter and has more efficiency in the biomass production of E. angustifolia.